Return of Goods in Online Buying and Selling Transactions (E-Commerce) on the Shopee Marketplace: A Hadith Perspective - Fikri Muhammad Hasan; Uswatun Hasanah; Hedhri Nadhiran (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2026)
Abstract Buying and selling is a primary and inseparable activity in human life. Along with the development of the times and increasing needs, business transaction methods have also undergone changes, marked by the emergence of online markets or marketplaces as digital buying and selling platforms. The convenience offered by online buying and selling is indeed very appealing; however, in practice, negligence and deviations that have the potential to harm one party still frequently occur. Although return policies exist as a form of protection for consumer and seller rights, in reality, various irregularities are still found in their implementation. This research is a library study conducted to directly examine the practice of product returns in online buying and selling transactions on the Shopee platform, viewed from the perspective of hadith. The data collection method used documentation techniques. The primary sources for this research come from hadith literature, while supplementary data were obtained from secondary references such as books, scientific journals, theses, articles, and information from online media. The findings of this research indicate that product returns in online transactions on Shopee are clearly regulated, and from the perspective of hadith, it is permissible in Islam if the goods are not as described or are defective, provided that honesty, justice, and mutual consent between the seller and buyer are prioritized. Keywords: Market Place; Online Buying and Selling; Return of Goods.   Abstrak Jual beli merupakan aktivitas utama dalam kehidupan manusia yang tidak dapat dipisahkan. Seiring dengan perkembangan zaman dan meningkatnya kebutuhan, metode transaksi bisnis juga mengalami perubahan, yang ditandai dengan hadirnya pasar online atau marketplace sebagai sarana jual beli digital. Kemudahan yang ditawarkan oleh jual beli online memang sangat menarik, namun dalam praktiknya, masih sering terjadi kelalaian dan penyimpangan yang berpotensi merugikan salah satu pihak. Meskipun terdapat kebijakan retur sebagai perlindungan hak konsumen dan penjual, kenyataannya masih ditemukan berbagai penyimpangan dalam penerapannya. Penelitian ini merupakan studi kepustakaan (library research) yang dilakukan untuk mendalami secara langsung praktik pengembalian barang dalam transaksi jual beli daring di platform Shopee, ditinjau dari perspektif hadis. Metode pengumpulan data menggunakan teknik dokumentasi. Sumber utama dalam penelitian ini berasal dari literatur-literatur hadis, sementara data pelengkap diperoleh dari referensi sekunder seperti buku, jurnal ilmiah, skripsi, artikel, serta informasi dari media daring. Temuan dalam penelitian ini menunjukkan bahwa return barang dalam transaksi online  Shopee telah diatur secara jelas  dan dalam persfektif hadis diperbolehkan dalam ilam jika barang tidak sesuai atau mengalami kecacatan  dengan mengutamakan kejujuran, keadilan dan kerelaa kedua belah pihak antara penjual dan pembeli. Kata Kunci: Jual Beli Online; Marketplace; Pengembalian Barang.